2000
DOI: 10.1345/aph.19174
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Selection for Hospitalized Patients with Presumed Community-Acquired Pneumonia: A Survey of Nonteaching US Community Hospitals

Abstract: Most hospitalized patients with CAP receive antimicrobial therapy consistent with the ATS guidelines. The addition of a macrolide may be associated with improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 11 publications
(2 reference statements)
3
66
1
1
Order By: Relevance
“…However, this variable was not subsequently selected in the multivariate model. Previous studies that analysed the influence of treatment on the duration of hospitalisation obtained discordant results [29,30]. Adherence, or not, to the SEPAR guidelines for the treatment of CAP did not relate significantly with LOS, as has been reported previously by the authors [31] and others [32].…”
Section: Discussionmentioning
confidence: 53%
“…However, this variable was not subsequently selected in the multivariate model. Previous studies that analysed the influence of treatment on the duration of hospitalisation obtained discordant results [29,30]. Adherence, or not, to the SEPAR guidelines for the treatment of CAP did not relate significantly with LOS, as has been reported previously by the authors [31] and others [32].…”
Section: Discussionmentioning
confidence: 53%
“…Although some earlier studies did not find differences in mortality according to compliance, 21 later reports found a higher mortality, even after adjusting for initial severity, when the treatment used did not comply with the guidelines. [22][23][24][25] However, on multivariate analysis, only initial treatment with quinolones (levofloxacin 89.5%) was independently associated with lower treatment failure, although this effect disappeared when early or late failure was analysed. The newer fluoroquinolones may have contributed to our findings because of their potency, broad spectrum covering S pneumoniae and atypical micro-organisms, and favourable phamacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment consistent with the ATS guidelines [27], for example, in which macrolides are recommended for atypical coverage, has been shown to significantly reduce length of hospitalisation as well as mortality from CAP [67,69,70].…”
Section: Community-acquired Pneumoniamentioning
confidence: 96%
“…A number of studies have shown that adherence to guidelines for empirical prescribing in CAP results in significant improvement in clinical outcome [67][68][69][70][71]. Treatment consistent with the ATS guidelines [27], for example, in which macrolides are recommended for atypical coverage, has been shown to significantly reduce length of hospitalisation as well as mortality from CAP [67,69,70].…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%